Technology-Mediated Communication in Familial Relationships: Moderated-Mediation Models of Isolation and Loneliness - Vanessa Burholt (The Gerontologist, 2020)
Background and ObjectivesWe examined whether technology-mediated communication has functional or emotional equivalence to face-to-face (FtF) contact in familial relationships, by scrutinizing the effects of phone, text/e-mail, and video contact on isolation and loneliness.Research Design and MethodsWe tested whether FtF contact with a relative would mediate the pathway between proximity to family and (i) isolation and (ii) loneliness. We then tested hypotheses that telephone, text/e-mails, and video contact would moderate this mediated pathway. We compared models for younger (<75) and older (≥75) cohorts, expecting to observe moderation effects for text/e-mail and video contact in the younger cohort only. Data were drawn from Wave 2 of CFAS Wales (United Kingdom) study (N = 2,099).ResultsProximity to a relative had a significant indirect effect on isolation and loneliness through the mediating variable FtF contact. Phone and text/e-mail contact moderated the effect of FtF contact on isolation for all samples. None of the technologies moderated the impact of FtF contact on loneliness for the full sample. Telephone contact had a moderating influence on loneliness for the younger cohort only. Video calls had no significant moderation effect.Discussion and ImplicationsTelephone and text/e-mail contact have functional equivalence to FtF contact in familial relationships. None of the forms of technological communication have emotional equivalence to the “gold standard” of embodied presence. The study demonstrates the importance of theorizing about the pathways to isolation and loneliness to better understand the likelihood of implementing successful interventions using technology-mediated communication within families.